ANALISIS GOOD MANUFACTURING PRACTICES (GMP) DI PANTI SOSIAL LANJUT USIA MANDALIKA - INDAH KARLINA; NOVIA ZURIATUN SHOLEHA; LINA YUNITA (Universitas Mahasaraswati K. Mataram, 2024)
Diseases transmitted through food or WHO calls them food-borne diseases (Food Borne Diseases) are infectious diseases or poisoning caused by microbes or agents that enter the body through the food consumed. This research aims to find out how GMP is implemented in food management at the Mandalika Social Home for the Elderly and recommend follow-up actions. This qualitative research uses a descriptive analysis approach. This research uses informants, namely nutritionists, as providers of information regarding the situation and conditions of the research setting with instruments as interview tools. Data analysis in this research uses the GAP Analysis method, namely to analyze the gaps that occur in the implementation of GMP at the Mandalika Elderly Social Home followed by recommending follow-up actions on aspects that have a low average score. This research shows that the implementation of GMP in the Mandalika Social Home for the Elderly is 79.59% with the highest implementation being in the aspects of materials, final products and packaging, namely 100%, while the lowest implementation is in the laboratory aspect, labels and product descriptions, training and record keeping with percentages by 40%.